Human Wharton's Jelly Mesenchymal Stem Cells Maintain the Expression of Key Immunomodulatory Molecules When Subjected to Osteogenic, Adipogenic and Chondrogenic Differentiation In Vitro: New Perspectives for Cellular Therapy - La Rocca, Giampiero; Lo Iacono, Melania; Corsello, Tiziana; Corrao, Simona; Farina, Felicia; Anzalone, Rita (Current Stem Cell Research & Therapy, 2013)
Rheumatoid arthritis and osteoarthritis are the main diseases that imply an inflammatory process at the joints involving the articular cartilage. Recently, mesenchymal stem cells (MSCs) derived from perinatal tissues were considered good candidates for cellular therapy of musculoskeletal and orthopaedic diseases, since they can differentiate into multiple cell types and are an easily accessible cellular source. Therefore, several protocols exist on the differentiation of mesenchymal stem cells of different origins into osteoblasts and chondrocytes. Another key feature of MSCs is their capacity to modulate the immune system responses in vitro and in vivo. This may have critical outcomes in diseases of the musculoskeletal system where an inflammatory or autoimmune process is at the basis of the main disease. In the present paper, after isolation of MSCs from Wharton's Jelly (WJ-MSCs), we performed the three standard differentiation protocols. The acquisition of the differentiated phenotype was demonstrated by the specific histological stains. As the main objective of this work, we determined the expression of immunomodulatory molecules (by immunohistochemistry and qualitative RT-PCR), both in undifferentiated cells and after differentiation. We demonstrated for the first time that immune-related molecules (as B7-H3/CD276 and HLA-E) which have been characterized in undifferentiated MSCs, are also expressed by the differentiated progeny. This strongly suggests that also after the acquisition of a mature phenotype, WJ-MSCs-derived cells may maintain their immune privilege. This evidence, which deserves much work to be confirmed in vivo and in other MSCs populations, may provide a formal proof of the good results globally achieved with WJMSCs as cellular therapy vehicle.
Keywords: tissue repair